A Review of the Website TeamScience.net - Aronoff, David M. (Marshfield Clinic, 2012)
As modern research methods have become more specialized and the true complexity of today’s most pressing health issues and diseases is revealed, collaborations among scientists trained in different fields have become essential for exploring and tackling these problems. This specialization of research methods has made interdependence, joint ownership, and collective responsibility between and among scientists near requirements. These features of team science may not suit everyone, but given these current trends, it is increasingly likely that most researchers will find themselves asked to participate on or lead a research team at some point in their careers. Bennett, Gadlin, Levine-Finley1